The socio-cultural world of women in medieval Andhra : from 11th to 13th centuries A.D. - Padma, A. (Delhi : Bharatiya Kala Prakashan, 2001)
Includes architectural renderings.
Includes bibliographical references and index.
Keywords: Women -- India -- Andhra Pradesh -- Social conditions